Efficiency analysis of state support measures for the small and medium-sized business sector in Russia during the pandemic - K. V. Glukhov; I. A. Chebashev; A. V. Mikhalevsky (Вестник университета)
A comprehensive analysis of legal and economic measures aimed at state support for small and medium-sized businesses during the COVID-19 pandemic is presented, as well as the relevant regulatory legal acts regulating certain aspects of credit anti-crisis support are studied in detail. Conclusions are presented on the state of the small and medium-sized business sector based on statistical data during the crisis period, and specific negative trends associated with the impact of the pandemic are highlighted. The emphasis is made on a detailed study of foreign experience in the field of anti-crisis measures to support small and medium-sized businesses. Within the framework of the article, such scientific research methods as analysis and generalization were used. It was noted, on the one hand, the high efficiency of anti-crisis support programs, on the other, its problems, including limited and insufficient budget funding.